Acculturation of Local Culture and Islamic Teachings in Bayan, North Lombok Regency A Review of Symbolic Interaction in Cultural Communication - Hamdani, Moya (Gema Wiralodra, 2024)
This research discusses the acculturation of local culture and Islamic teachings and how it is practiced in daily life in Bayan, North Lombok Regency. The purpose of this research is to find the acculturation of culture and Islamic teachings as well as the meaning of symbols agreed upon by the community in practice by the Sasak people of the Bayan tribe. This research is a descriptive analysis type of qualitative research. The subjects of this research are traditional leaders and community leaders who are native Bayan people who know the ins and outs of Islam in Bayan. The data collection techniques used are observation, interview, documentation. Then the data analysis techniques used are data reduction, data presentation, and conclusion drawing (Verification). The results showed that the understanding of animism and dynamism of the Bayan community before knowing Islam contributed to a new culture in the religious practices of Wetu Telu Islam. In practice, Wetu Telu Islam is different from the real teachings of Islam. Customary rituals must be involved in the practice of Islam so that their perception of performing religious rituals means following the traditions of the ancestors practiced for generations. Symbolic meaning in the symbols of Wetu Telu Islamic rituals is carried out by each individual actively and voluntarily, so that in the end each individual has a role in the implementation of the ritual. The communication process then occurs in the formation of the role. so that the wider bayan community privileges the meaning behind the Wetu Telu Islamic symbols.